EFEK MEDIASI EMPLOYEE ENGAGEMENT PADA HUBUNGAN ANTARA SERVANT LEADERSHIP DAN KINERJA DOSEN PADA PERGURUAN TINGGI DI MOJOKERTO (Employee Engagement Effect on the Relationship between Servant Leadership and Lecturer Performance at Universities in Mojokerto) - Ade Setia Pratama; Tatang Ary Gumanti (Pascasarjana Universitas Halu Oleo, 2019)
Human resource management in educational organization as it get longer, the demands getting higher and the problem getting more complex, that is how it happen on university level of study. One of the most important key to form a successful organization depends on achievement and performance of each personnel inside. Those achievements including the role of good leader who is understand what his subordinate wants and it reflected on leader’s attitude as servant leadership and good commitment also high enthusiasm of employee toward their organization reflected on their attitude known as employee engagement. The purpose of this research is to understand how big the effect of employee engagement as relationship mediator between servant leadership and lecture performance on some universities in Mojokerto. This research using quantitative approach, data collection using questionnaire which spreads during July until September 2017, 80 lecturers as a sample respondent and they are come from four universities in Mojokerto, and it analyzed using path analysis. Result of this research indicates that employee engagement does not able to relationship mediator between servant leadership and lecturer performance. Furthermore, most of the respondent explained that servant leadership will have more impact on performance without employee engagement. Therefore in this research servant leadership has dominant role on influencing lecturer performance to improve overall organization performance. Keywords: Kinerja dosen, Servant leadership, Employee engagement